Biophysical Suitability of Dondon Beach for Recreational Beach Tourism in Central Lombok, Indonesia - Fahria, Nur; Amir, Sadikin; Wahyudi , Rhojim; Waspodo , Saptono (Jurnal Biologi Tropis, 2026)
Dondon Beach in Mertak Village, Central Lombok, is a potential site for recreational beach tourism, but site-specific evidence of its biophysical suitability remains limited. This study assessed tourism suitability and identified the main supporting and limiting factors across three stations representing the western, central, and eastern beach sectors. Field surveys were conducted in March–April 2026. Ten parameters—water depth, beach type, beach width, bottom substrate, current velocity, beach slope, relative water transparency, coastal land cover, hazardous biota, and distance to freshwater—were evaluated using the Tourism Suitability Index (Indonesian: Indeks Kesesuaian Wisata, IKW) with normalized weights. The calculated IKW values were 2.52, 2.80, and 2.62 for Stations 1, 2, and 3, respectively, placing all stations in the highly suitable category (S1). Suitability was supported by white sand, adequate beach width, high relative water transparency, and proximity to freshwater. Deeper water, moderate slopes, gravelly sand at one station, localized sea urchins, and spatial variation in current velocity require safety-based management. These findings indicate biophysical suitability but do not alone establish sustainable tourism feasibility; additional assessments of ecological carrying capacity, seasonal variability, visitor safety, infrastructure readiness, and community acceptance are required.